Self Concept, Social Support, and Anxiety in Dealing with Fractured Patient - Dini Kurniawati (Jurnal Ners, 2012)
Introduction: The self-concept on fractured-patient is the way of the patient views himself as a whole. The view may cause the patient to feel less confident and may lead the patient to experience anxiety. Such condition requires serious attention in the form of social support. The objective of this research was to identify the association of the self-concept, social support, and anxiety in dealing with fracturedpatient.Methods: This research employed correlational design. The samples of this research were in-patients who suffered from femur fractures, underwent treatments for at least three days, aged 25–45 and were conscious and, willing to be involved in the research. The technique used in this research was purposive sampling.Result: Results of the research, when analyzed statistically using the regression analysis, revealed that the correlation between the self-concept and anxiety generated rx1y = –0.476 with p = 0.007 (p < 0.01). Furthermore, the correlation between social support and anxiety generated rx2y = –0.531 with p = 0.003 (p < 0.01) while the correlation among self-concept, social support, and anxiety generated F = 4,758 at p = 0.009 (p < 0.01). The determination coeffi cient (R2) = 0.293 while the figures of the effective contribution (EC) were as follows: the effective contribution (EC) of the self-concept to anxiety was 1.051%, while the effective contribution (EC) of the social support to anxiety was 28.216%.Conclusion: The higher the one’s self-concept, the lower the anxiety level would be, and vice versa. The same thing applied to the relation between social support and anxiety. The higher the social support one got, the lower the anxiety level would be. The correlation between self-concept and social support and anxiety in dealing fractured patient existed. Self-concept contributed to anxiety. According to the behavioral theories, anxiety arouses from one’s fear of being rejected or not being accepted in terms of interpersonal relationship. Therefore, the high self-concept (high self acceptance) lowers the fear for rejection (anxiety).